Effect of the trm reinforcement ratio on the lateral response of a three-story masonry-infilled rc frame retrofitted with trm - Fillipou, Christiana; Chrysostomou, Christis; Kyriakides, Nicholas (My University, 2021)
This paper aims to expand today’s knowledge regarding the use of TRM, which is a combination of inorganic matrix (lime-or cement-based) and non-corrosive multi-axial textile fabrics, for retrofitting masonry-infilled RC frames. Firstly, a 2D simple FE micro-model of a three-story masonry-infilled RC frame with TRM is developed and validated using the results obtained from a past experimental study. A parametric study is then performed aiming to examine the influence of the TRM reinforcement ratio on the behavior of the three-story masonry-infilled RC frame retrofitted with TRM under cyclic loading. Different number of TRM layers and different geometry of the textile reinforcement on each floor of the three-story masonry-infilled RC frame with TRM are used. Based on the numerical results presented in this paper, conclusions regarding the effectiveness of using the TRM composite material for retrofitting infilled frames are drawn. © Fédération Internationale du Béton (fib) – International Federation for Structural Concrete.
Keywords: Reinforcement ratio; Textile-Reinforced Mortar; Cyclic loading; Infilled frames; Numerical modelling